2019
DOI: 10.1108/gs-06-2019-0020
|View full text |Cite
|
Sign up to set email alerts
|

Grey relational evaluation of impact and control of malaria in Sub-Saharan Africa

Abstract: Purpose The rise in malaria deaths discloses a decline of global malaria eradication that shows that control measures and fund distribution have missed its right of way. Therefore, the purpose of this paper is to study and evaluate the impact and control of malaria on the independent states of the Sub-Saharan African (SSA) region over the time period of 2010–2017 using Deng’s Grey incidence analysis, absolute degree GIA and second synthetic degree GIA model. Design/methodology/approach The purposive data sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“… To the best of the authors' knowledge, concerning the prioritization of the barriers to international MBA enrolment using the GIA method, no such formal contribution has been found. However, in other fields, GIA has been employed in classification and ranking studies [15].  This study further recommends the policy recommendation for improving the enrolment in higher education by reducing the barriers.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“… To the best of the authors' knowledge, concerning the prioritization of the barriers to international MBA enrolment using the GIA method, no such formal contribution has been found. However, in other fields, GIA has been employed in classification and ranking studies [15].  This study further recommends the policy recommendation for improving the enrolment in higher education by reducing the barriers.…”
Section: Introductionmentioning
confidence: 88%
“…The Deng GIA model measures the similarity between system factors by determining the grey relational grade. This parameter represents the level of correlation between a reference sequence and other sequences that are being compared to it [53].…”
Section: Deng's Grey Incidence Analysis Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Grey System Theory was established by Professor Deng in 1982, and since then, it has seen its application in a wide range of areas, e.g., healthcare (Aydemir & Sahin, 2019;Quartey-Papafio et al, 2019), environmental sustainability (Shahzad et al, 2020), supply chain (Diba & Xie, 2019;Mahmoudi et al, 2021a;2021b), tourism (Javed et al, 2020a) energy and emissions (Ofosu-Adarkwa et al, 2020;Du et al, 2019;Xie et al, 2020), information systems (Esangbedo et al, 2021), engineering (Abifarin et al, 2021), economics (Camelia, 2015), etc. Also, it has seen applications in project management Mahmoudi et al, 2020; Studies have reported that Grey System Theory based models are particularly useful when data is small or insufficient (Javed et al, 2020b), as is the case in the current study.…”
Section: Grey Absolute Decision Analysis (Gada)mentioning
confidence: 99%
“…The grey information is GS 11,3 an obstacle to serve effective decision, and thus grasping grey information from system characteristics is enrolled in present work. Grey information is crucial for strategic network formation and deals with unclear, vague inaccurate and imprecise information, which exist in the system and can be utilize to make decision-making effectively (Liu et al, 2018;Javed and Liu, 2018;Mahmoudi, 2018;Salookolaei et al, 2018;Quartey-Papafio et al, 2019;Lui, 2019;Darvishi et al, 2019;Liu and Yang, 2019;Qian et al, 2019).…”
Section: Advanced Manufacturing Machinesmentioning
confidence: 99%